Procalcitonin as a sepsis marker: experience of an intensive care setting in Malaysia - Mat Nor, Mohd Basri; Md Ralib, Azrina; Mohamed, Abdul Hadi; Abdullah, Nor Zamzila (Ministry of Health and Universiti Brunei Darussalem, 2013)
Introduction: During infection, there is increased expression of CALC-I gene resulting in ubiquitous release of procalcitonin (PCT). Since the expression of PCT is dependent on the genetic constituents of a population, this study aimed to validate the diagnostic performance of PCT in differentiating sepsis from noninfectious systemic inflammatory response syndrome (SIRS) in a Malaysian intensive care unit (ICU). Materials and Methods: Ninety-five patients fulfilling the criteria for SIRS were enrolled. Daily concentrations of PCT, C-reactive protein (CRP) and white cell count (WCC) were measured over three days. The diagnostic and predictive performance of these biomarkers were assessed using area under the curve of the ROC. Results: In this study, medical and surgical cohorts had similar PCT concentrations. Peak (p=0.02) and daily PCT (p<0.001) concentrations were significantly higher in patients with sepsis compared to SIRS. There were no significant differences in the CRP and WCC concentrations between the two groups. Peak PCT was significantly higher in patients with bacteraemia than those without (49.1 [19.3- 57] vs. 6.9 [1.1-25.6 ng/ml], p=0.001). PCT was diagnostic of sepsis and bacteraemia (AUC of 0.73 [0.64-0.83] and 0.80 [0.66-0.93] respectively). Peak PCT was significantly higher in septic patients with culture positive compared to culture negative (p=0.02). At the optimal cut-point of 10.68 ng/ml for peak PCT, sepsis was very likely with specificity of 86% and psotive predictive value (PPV) of 91%. There was a good correlation between PCT concentration and the Sequential Organ Failure Assessment (SOFA) score in the sepsis cohort (r=0.62, p<0.0001). Conclusion: PCT was better than CRP or WCC in differentiating sepsis from non-infectious SIRS in critically-ill patients. PCT is diagnostic of sepsis and bacteraemia, and is also useful as an indicator of severity of organ failure in sepsis.